Techno-economic Review of Isolation of Eugenol from Clove Oil with Batch Distillation - Sugiharto, Agung; Harismah, Kun; Sekarwati, Erni; Widayatno, Tri (Jurnal Rekayasa Kimia & Lingkungan, 2024)
All parts of the clove plant (Syzygium aromaticum L.), including roots, stems, leaves and flowers, can be processed into clove oil. One of the important compounds in clove oil is Eugenol. Pharmaceutical grade eugenol has a very high selling value, however conventional refining without a purification process only produces clove oil with a eugenol content of 78-80%. In this research, the purification of eugenol from clove oil refined by clove farmers was carried out by comparing two methods, namely the reactive extraction process and batch distillation. Analysis of the final products from both processes was carried out by GC-MS. The eugenol isolation process using a reactive extraction method with various variations in NaOH purity obtained optimum results at 2 N NaOH levels where clove oil was produced with a eugenol content of 75.33% with a product recovery of 40%. Meanwhile, eugenol was isolated using batch distillation with constant reflux and atmospheric pressure to obtain pure clove oil with a eugenol content of 97.02% with a product recovery of 28.25%.